2004
DOI: 10.1037/0022-006x.72.2.202
|View full text |Cite
|
Sign up to set email alerts
|

Partner Violence Before and After Couples-Based Alcoholism Treatment for Male Alcoholic Patients: The Role of Treatment Involvement and Abstinence.

Abstract: This study examined partner violence before and after behavioral couples therapy (BCT) for 303 married or cohabiting male alcoholic patients and used a demographically matched nonalcoholic comparison sample. In the year before BCT, 60% of alcoholic patients had been violent toward their female partner, 5 times the comparison sample rate of 12%. In the 1st and 2nd year after BCT, violence decreased significantly from the year before BCT, and clinically significant violence reductions occurred for patients whose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
176
0
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(193 citation statements)
references
References 49 publications
14
176
0
3
Order By: Relevance
“…In addition, this research has demonstrated that alcoholics who relapsed did not reduce their violence, whereas alcoholics in remission did reduce their violence (O'Farrell & Murphy 1995). In addition, O'Farrell et al (2004) found that couple's involvement with behavioral couples treatment (BCT) was predictive of lower post-treatment partner violence in alcoholic men, and mediation analyses suggested that relationship functioning and drinking mediated this relationship. Similarly, Fals-Stewart et al (2002) found that among drug abusing men, many with alcohol problems, behavioral couple's therapy reduced their violence from pre-treatment (43%) to posttreatment (17%).…”
Section: Alcohol and Intimate Partner Violence: When Can We Say That mentioning
confidence: 91%
“…In addition, this research has demonstrated that alcoholics who relapsed did not reduce their violence, whereas alcoholics in remission did reduce their violence (O'Farrell & Murphy 1995). In addition, O'Farrell et al (2004) found that couple's involvement with behavioral couples treatment (BCT) was predictive of lower post-treatment partner violence in alcoholic men, and mediation analyses suggested that relationship functioning and drinking mediated this relationship. Similarly, Fals-Stewart et al (2002) found that among drug abusing men, many with alcohol problems, behavioral couple's therapy reduced their violence from pre-treatment (43%) to posttreatment (17%).…”
Section: Alcohol and Intimate Partner Violence: When Can We Say That mentioning
confidence: 91%
“…Sin embargo, a pesar de las críticas señaladas, algunos estudios estadounidenses (Chase, O´Farrell, Murphy, FalsStewart, y Murphy, 2003;Fals-Stewart, Kashdan, O´Farrell, y Birchler, 2002;O'Farrell, Van Hutton, y Murphy, 1999;O´Farrell, Murphy, Stephan, Fals-Stewart, y Murphy, 2004) han valorado la eficacia de la denominada terapia conductual de pareja para el tratamiento de la violencia de géne-ro en población drogodependiente. Uno de los principales estudios en este sentido es el desarrollado por O'Farrell et al (2004), con una muestra de 303 hombres alcohólicos que participaron, junto con sus parejas, en un programa de terapia conductual de pareja.…”
Section: Programas Basados En Terapia De Parejaunclassified
“…En esta investigación se utilizó también un grupo de control, compuesto también por 303 parejas, sin problemas de alcohol. Todas las parejas de la muestra recibieron una intervención conductual, basada en el programa desarrollado por el grupo de O'Farrell y Fals-Stewart (O'Farrell y Fals-Stewart, 2000;O´Farrell, et al, 2004). Se trata de un programa compuesto por 20-22 sesiones, de carácter semanal, aplicadas durante un período de entre 5 y 6 meses.…”
Section: Programas Basados En Terapia De Parejaunclassified
“…For some couples, drinking behavior is closely associated with domestic violence (e.g., Leonard, Bromet, Parkinson, Day, & Ryan, 1985;Pan et al, 1994). Therefore, substance use treatment may promote positive change, and there is evidence that interventions reducing alcohol use for male alcoholic patients are associated with reduced violence (O'Farrell, Murphy, Stephan, Fals-Stewart, & Murphy, 2004). In addition, Capaldi et al (2006) found that children are frequently present during violent incidents --at close to one half of the cases resulting in an arrest for the Oregon Youth Study sample.…”
Section: A Dynamic Developmental Systems Approach To Understanding VImentioning
confidence: 99%
“…Although relatively scarce, there are a number of treatment and intervention programs that focus on the couple (Hamel, 2005;O'Farrell et al, 2004;O'Leary, 1996). Brannen and Rubin (1996) compared gender specific treatment (GST) with conjoint (couple) treatment for courtmandated men.…”
Section: Implications For Future Research and Clinical Interventionsmentioning
confidence: 99%